Impact of Transmission Scheme of Visible Solar Radiation on Temperature and Mixing in the Upper Water Column With Inputs for Transmission Derived From Ocean Color Remote Sensing. Issue 7 (30th June 2020) - Liu, Tongtong; Lee, Zhongping; Shang, Shaoping; Xiu, Peng; Chai, Fei; Jiang, Mingshun
Abstract: The penetration of visible solar radiation (VSR) in the upper ocean contributes to heating in the upper water column, and this process is modulated by constituents in water such as phytoplankton. Various schemes have been developed to propagate surface VSR to deeper depths, which are incorporated in ocean circulation models to study basin‐scale impacts on ocean and atmosphere by phytoplankton. However, none of these studies evaluated sensitivity of the schemes of VSR transmission to upper‐water dynamics, especially when the required input is derived from ocean color remote sensing. We used an idealized one‐dimensional (1‐D) Regional Ocean Modeling System (ROMS) to simulate profiles of upper water column temperature at six locations with different ocean color characteristics (containing different water constituents). We incorporated and tested four different schemes of VSR transmission: the default water‐type scheme within the ROMS, two schemes based on concentrations of chlorophyll (Chl), and one scheme based on water's inherent optical properties (IOPs). The results showed that, although using the same ocean color information and the same circulation model, the IOPs‐ and Chl‐based schemes resulted in very different vertical temperature and upper‐water mixing compared to those using the default scheme, with differences in sea surface temperature up to 1.5–2°C. These results highlight the importance of developing and incorporating more appropriate VSR transmission schemes into large‐scale ocean circulation simulations, where the inputs for the transmission are inherently estimates from ocean color—the actual measurement from satellite remote sensing. Plain Language Summary: Solar irradiance is the most important energy source for the Earth. In the past decades, many transmission schemes were developed to quantify the penetration of visible solar radiation (VSR) in the upper ocean, which were incorporated into general circulation models to evaluate the effects of VSR on upper‐ocean and atmospheric dynamics. In this work, we incorporate four different transmission schemes (one based on water type; one based on inherent optical properties, or IOPs based; and two based on chlorophyll concentration, or Chl based) in a one‐dimensional ocean general circulation model. We found that, although all transmission schemes used the same data from ocean color remote sensing—the source to derive the required input for the transmission schemes, the IOPs‐ and Chl‐based schemes resulted in very different vertical temperature and upper‐water mixing, which were also different from those based on water type. Because the VSR profiles estimated based on IOPs are more accurate for oceanic and coastal waters, these results advocate the application of IOPs products from ocean color satellite to study upper‐ocean dynamics in the global oceans and related air‐sea interactions. Key Points: Impact of transmission scheme of visible solar radiation (VSR) on temperature and mixing in the upper ocean is investigated The required input (chlorophyll or inherent optical properties) for the scheme is derived from the same ocean color remote sensing Different VSR transmission schemes can lead to significant differences in vertical temperature profile, although all use the same color data